2004
DOI: 10.1186/1472-6874-4-9
|View full text |Cite
|
Sign up to set email alerts
|

A survey of relationship between anxiety, depression and duration of infertility

Abstract: BackgroundA cross sectional study was designed to survey the relationship between anxiety/depression and duration/cause of infertility, in Vali-e-Asr Reproductive Health Research Center, Tehran, Iran.MethodsAfter obtaining their consents, 370 female patients with different infertility causes participated in, and data gathered by Beck Depression Inventory(BDI) and Cattle questionnaires for surveying anxiety and depression due to the duration of infertility. This was studied in relation to patients' age, educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

37
188
8
16

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(249 citation statements)
references
References 32 publications
37
188
8
16
Order By: Relevance
“…It was noticed that women with short period (less than three years) of infertility suffered less and had lower psychological distress than those with a long period (three or more than three years) of infertility. These findings contradict with the result of Kee et al (2000) who stated that based on depression scales, infertile patients who had infertility for an intermediate to a long time showed less symptoms than those who are in their first stage of their problem, [61] while in agreement with the findings of other studies as Al-Homaidan (2011) and Ramezanzadeh et al (2004) who showed that psychological distress in infertile women increase with time & depression peaks between the second and third year of infertility and does not come back to normal range until after six years of infertility. [43,54] A longer time period of infertility and repeated, referring to the physicians, infertility would gradually shift to a chronic problem; thus confronting this problem, the infertile women would have experienced monthly cycles of hope and hopelessness, their stress, and depression severity would decrease but would never disappear.…”
Section: Published By Sciedu Presscontrasting
confidence: 64%
See 2 more Smart Citations
“…It was noticed that women with short period (less than three years) of infertility suffered less and had lower psychological distress than those with a long period (three or more than three years) of infertility. These findings contradict with the result of Kee et al (2000) who stated that based on depression scales, infertile patients who had infertility for an intermediate to a long time showed less symptoms than those who are in their first stage of their problem, [61] while in agreement with the findings of other studies as Al-Homaidan (2011) and Ramezanzadeh et al (2004) who showed that psychological distress in infertile women increase with time & depression peaks between the second and third year of infertility and does not come back to normal range until after six years of infertility. [43,54] A longer time period of infertility and repeated, referring to the physicians, infertility would gradually shift to a chronic problem; thus confronting this problem, the infertile women would have experienced monthly cycles of hope and hopelessness, their stress, and depression severity would decrease but would never disappear.…”
Section: Published By Sciedu Presscontrasting
confidence: 64%
“…However, this result was in line with the study done by Noorbala et al (1999) which found that the rate of psychological disorder was higher among working women. [53] It was contradicted what Upkong (2006) and Ramezanzadeh et al (2004) found in their study. They found that depression and/or anxiety were observed more in housewives than in outside employees.…”
Section: Published By Sciedu Pressmentioning
confidence: 71%
See 1 more Smart Citation
“…Semen quality, frequency of ejaculation and sperm functions gradually decrease with advancing age. Moreover, the spermatozoa from older men have increased incidence of abnormalities and many children born from older men have an increased chance of abnormalities [26].…”
Section: Discussionmentioning
confidence: 99%
“…Ramezanzadeh et al [25] clarified that in Islamic and eastern countries such as Iran, family status especially childbearing is very important and valuable. In Egyptian culture, negative attitude toward infertility are so miserable.…”
Section: Discussionmentioning
confidence: 99%